2010
DOI: 10.1080/0376835x.2010.508604
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Kaunda's plan for self-sufficiency: Is urban agriculture finally beginning to receive support in Zambia?

Abstract: Urban agriculture has become one of the key survival strategies for the urban poor in the developing world. Yet most cities do not have policy to support it and many actively discourage it. This paper reviews the situation in Zambia's four largest cities. During the 1960s-1970s, the Kaunda government attempted to create a supportive policy environment for urban agriculture, which included support for peri-urban cooperatives. However, the current situation reveals that a near absence of institutional support fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Considerable policy controversy continues to surround urban agriculture in the global South (Foeken 2006;Mubvani and Mushamba 2006;Thornton et al 2010). Some African observers view urban agriculture as "one of the most exciting concepts of sustainable development since it addresses almost all areas of sustainability" (Adedeji and Ademiluyi 2009, p. 45).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Considerable policy controversy continues to surround urban agriculture in the global South (Foeken 2006;Mubvani and Mushamba 2006;Thornton et al 2010). Some African observers view urban agriculture as "one of the most exciting concepts of sustainable development since it addresses almost all areas of sustainability" (Adedeji and Ademiluyi 2009, p. 45).…”
Section: Resultsmentioning
confidence: 99%
“…As a whole, it is acknowledged that urban agriculture can be one part of a livelihood strategy for the urban poor, especially in the growing urban centres of Africa (Tevera 1996;Lourenco-Lindell 1997;Mtani 1997;Smith and Tevera 1997;Brock and Foeken 2006;Hampwaye et al 2007;Simatele and Binns 2008;Thornton et al 2010).Women are potentially core beneficiaries of support programmes for urban agriculture, especially in Africa. Lee-Smith (2006) shows that the predominance of women farmers in sub-Saharan Africa is attributed to the fact that women often bear the main responsibility for household subsistence and well-being as well as their lower educational levels than men and thus reduced prospects for other employment opportunities.…”
Section: Key International Policy Debatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Simataa and Musuka (2013) also reported that O. niloticus was the fastest growing bream in Zambia, harder and more resistant than O. andersonii and because 70% of its diet was plankton it was easier and cheaper to feed, as such the fish grew faster, especially the males, which gave the farmers good returns. According to Thornton et al (2010), Oreochromis niloticus has been particularly prevalent; however it reigns more prominently outside of Africa. Within Africa O. niloticus is more of a delicacy, although many rural villagers use it as a protein supplement for their meager diets.…”
Section: Fish Species Cultured By Farmersmentioning
confidence: 99%